Spatio-Temporal Evolution and Quality Analysis of Construction Land in Urban Agglomerations in Central China - Ning, Qimeng; Ouyang, Xiao; Liu, Shaobo (Frontiers in Ecology and Evolution, 2022)
Understanding the pattern and quality of construction land expansion in urban agglomerations is important for new urbanization and high-quality development of land spaces. Taking urban agglomeration in the middle reaches of the Yangtze River as the research object, this study analyzes the spatio-temporal pattern and quality level of construction land expansion at various scales using remote sensing images, the expansion intensity index, the coordination degree model, and the Tapio elastic decoupling model. The results show that from 2000 to 2020, (1) the construction land scale of urban agglomeration in the study area had expanded, with significant stage characteristics and spatial differentiation patterns. (2) The overall relationship between the construction land and the population in urban agglomerations was found to be uncoordinated, but the coordination degree had been improved. The optimization of human–land coordination was faster at the metropolitan scale than at the overall level and the sub-urban agglomerations. (3) The decoupling relationship between the overall construction land and the economy in urban agglomerations was weak and had improved. The coupling/decoupling relationship was found to be better at the metropolitan scale than at the overall level and sub-urban agglomerations.